PUBLIC SECTOR EFFICIENCY ON EDUCATION AND HEALTH; EVIDENCE FROM EAST JAVA - Rifai Afin (Trunojoyo University of Madura, 2008)
In this paper we analyze public sector efficiency in the East Java Regions. After a conceptual discussion of expenditure efficiency measurement issues, we compute efficiency scores and rankings by applying a range of measurement techniques that is DEA (Data Envelopment Analysis). Another method that we used in this paper to measure the efficiency is the Stochastic Frontier Analysis (SFA). The study finds that expenditure efficiency on education and health across regions in East Java member states is rather diverse especially as compared to the group of top performing emerging markets in Indonesia. SFA model applied both time invariant and time varying decay. The estimation process yields differences on the education and health sector. In the education sector model, per capita expenditure on education doesn't significant in the education SFA model but per capita expenditure on health has significant impact on percentage of health people as a output in the SFA model. The estimation for DEA scores yields different in significant parameter and estimation technique (fixed or random) to get the best parameter.